PENGAWASAN LALU LINTAS LAUT DAN DARAT DI DINAS PERHUBUNGAN KABUPATEN KEPULAUAN MERANTI - Suhaimi; Mulyadi, Edi; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
The Meranti Islands Regency is an archipelago with strategic yet complex geographic characteristics, where interregional connectivity is highly dependent on the integration of sea and land traffic. This study aims to analyze the effectiveness of sea and land traffic supervision conducted by the Meranti Islands Regency Transportation Agency and identify obstacles to the implementation of this policy. The methodology used in this study is descriptive qualitative with an empirical juridical approach. Data collection techniques were conducted through field observations, in-depth interviews with the Transportation Agency, and documentation studies related to regional transportation regulations. The results indicate that sea traffic supervision focuses on shipping safety and the operation of public ports, while land supervision focuses on road transportation order and road safety facilities. However, the effectiveness of supervision is still hampered by limited personnel with special certifications, a lack of supporting infrastructure (such as patrol boats and vehicle testing equipment), and the vast and difficult-to-reach geographical area. It is concluded that strengthened cross-sectoral coordination and increased budget allocation are needed to modernize the information technology-based supervision system to achieve safe and orderly transportation in the Meranti Islands Regency. Keywords: Supervision, Traffic, Transportation Agency, Meranti Islands, Transportation Safety.